Baseline blood pressure does not modify the effect of intravenous thrombolysis in successfully revascularized patients - Xiaoxi, Zhang; Xuan, Zhu; Lei, Zhang; Zifu, Li; Pengfei, Xing; Hongjian, Shen; Yongxin, Zhang; Weilong, Hua; Yihan, Zhou; Dongwei, Dai; Qiang, Li; Rui, Zhao; et al. (Frontiers in neurology, 2022)
Studies indicate a trajectory relationship between baseline blood pressure (BP) and outcome in patients with acute ischemic stroke (AIS) eligible for both intravenous thrombolysis (IVT) with alteplase and endovascular treatment (EVT). We determined whether baseline BP modified the effect of IVT in successfully revascularized AIS patients who participated in the Direct Intra-Arterial Thrombectomy to Revascularize AIS Patients With Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals (DIECT-MT) trial.BackgroundStudies indicate a trajectory relationship between baseline blood pressure (BP) and outcome in patients with acute ischemic stroke (AIS) eligible for both intravenous thrombolysis (IVT) with alteplase and endovascular treatment (EVT). We determined whether baseline BP modified the effect of IVT in successfully revascularized AIS patients who participated in the Direct Intra-Arterial Thrombectomy to Revascularize AIS Patients With Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals (DIECT-MT) trial.The association of baseline systolic BP, trichotomized as high (141-185 mmHg), middle (121-140 mmHg), and low (91-120 mmHg), and the outcomes of any intracerebral hemorrhage (ICH), symptomatic ICH (sICH), and mortality and functional outcome on the modified Rankin scale at 90 days were explored. Logistic regression models determined the interaction between clinical outcomes and baseline systolic and diastolic BP, and mean arterial pressure (MAP), at 10 mmHg intervals. Data are reported as odds ratios (OR) and 95% CI.MethodsThe association of baseline systolic BP, trichotomized as high (141-185 mmHg), middle (121-140 mmHg), and low (91-120 mmHg), and the outcomes of any intracerebral hemorrhage (ICH), symptomatic ICH (sICH), and mortality and functional outcome on the modified Rankin scale at 90 days were explored. Logistic regression models determined the interaction between clinical outcomes and baseline systolic and diastolic BP, and mean arterial pressure (MAP), at 10 mmHg intervals. Data are reported as odds ratios (OR) and 95% CI.A post-hoc analysis of DIRECT-MT, in 510 of the 656 randomized participants with successful revascularization underwent MT. The overall adjusted common OR of IVT and baseline BP on any ICH, sICH, and 90-day mortality and functional outcome were 0.884 (95%CI 0.613-1.274), 0.643 (95%CI 0.283-1.458), 0.842 (95%CI 0.566-1.252), and 1.286 (95%CI 0.772-2.142), respectively. No significant interaction between baseline blood pressure and intravenous thrombolysis with clinical outcome was observed.ResultsA post-hoc analysis of DIRECT-MT, in 510 of the 656 randomized participants with successful revascularization underwent MT. The overall adjusted common OR of IVT and baseline BP on any ICH, sICH, and 90-day mortality and functional outcome were 0.884 (95%CI 0.613-1.274), 0.643 (95%CI 0.283-1.458), 0.842 (95%CI 0.566-1.252), and 1.286 (95%CI 0.772-2.142), respectively. No significant interaction between baseline blood pressure and intravenous thrombolysis with clinical outcome was observed.In patients with baseline SBP under 185 mmHg, baseline blood pressure does not alter the risk of hemorrhagic transformation and clinicaloutcome in successfully revascularized patients, regardless of intravenous alteplase usage. Future studies are needed to confirm our findings.ConclusionsIn patients with baseline SBP under 185 mmHg, baseline blood pressure does not alter the risk of hemorrhagic transformation and clinicaloutcome in successfully revascularized patients, regardless of intravenous alteplase usage. Future studies are needed to confirm our findings.URL: http://www.clinicaltrials.gov, Identifier: NCT03469206.RegistrationURL: http://www.clinicaltrials.gov, Identifier: NCT03469206.